Effect of non-nutritive sweeteners, chemical preservatives and antioxidants on microbial and sensory characteristics of dehydrated guava - Khattak, Muhammad Muzaffar Ali Khan; Ayub, Muhammad; Zeb, Alam; Ullah, Javid (University of Peshawar, 2005)
A study was carried out to evaluate the effect of various concentrations of non nutritive sweeteners individually and in combination along with chemical preservatives i.e. potassium metabisulphite (PMS) and potassium sorbate (PS) and anti-oxidants including citric acid (CA) and ascorbic acid (AA) on microbial and sensory characteristics of dehydrated guava slices during 90 days storage. The solutions of saccharine, cyclamate, aspartame and their mixture were prepared in different concentrations. Guava slices were submerged in these sweeteners for a 24 hour and subsequently cabinet dehydrated to a final moisture content of 25%. Total microbial count (TMC) were recorded in all samples however, samples treated with AA, CA and PMS showed negligible microbial population than PS during storage. Guava slices treated with non-nutritive sweeteners were leathery in appearance due to severe loss of moisture. Comparatively the slices treated with PMS and AA showed highest overall acceptability. The statistical analysis showed that storage intervals and sweeteners had a significant effect (p<0.05) on TMC and organoleptic quality of dehydrated guava slices.